Favorable Interfacial Chemomechanics Enables Stable Cycling of High-Li-Content Li–In/Sn Anodes in Sulfide Electrolyte-Based Solid-State Batteries - Hänsel, Christian (American Chemical Society (ACS), 2021)
10.1021/acs.chemmater.1c01431